Prestasi keusahawanan koperasi kariah masjid di Semenanjung Malaysia - Abdul Rahim, Abdul Rahman (2024)
The status of the inactive entrepreneurial performance of the Mosque Community Cooperative (KKM) remains unclear, and previous studies indicate that further scientific research is needed to substantiate it. The objectives of this study are: first, to evaluate the current entrepreneurial performance status of inactive KKMs, second, to determine the differences in entrepreneurial performance between inactive and active KKMs; third, to develop a model that reflects the entrepreneurial performance of both inactive and active KKMs; and fourth, to predict the significance of entrepreneurial performance criteria for inactive and active KKM in the future. A total of 221 samples were taken from KKM chairpersons across Peninsular Malaysia. Data from the survey were analyzed using mean analysis techniques, T-test, Pearson correlation and multivariate regression. The main finding of the study shows that the overall mean for inactive KKM status is 4.35, which is at a moderately good level. In comparing inactive and active KKMs, this study found a significant difference in entrepreneurial performance with a p-value of 0.001 (p< 0.05). For the entrepreneurial practice model of inactive versus active KKMs, the study found no significant difference in the current implementation. Additionally, the study also found that certain criteria for entrepreneurial performance in both inactive and active KKMs will remain unchanged; however, most are predicted to change in the future. Therefore, this study suggests that both inactive and active KKM entrepreneurs enhance their knowledge in business, organizational management and self-improvement.